2010
DOI: 10.1002/chem.201001238
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrolled Manipulation of a Microscale Object: A Rotational or Translational Mechanism

Abstract: In this paper the photocontrolled manipulation of solid materials on the surface of a liquid crystalline thin film is described. Three different types of films namely cholesteric liquid crystal (ChLC), compensated nematic liquid crystal (NLC) and nematic LC were used. The rotational and translational manipulation of the microscale solid object was induced by irradiation of light and mode of manipulation (either translational or rotational) was changed by changing the isomer of the azobenzene compound used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…However, as shown in Fig.4 (b), when the Az-doped samples were irradiated with Ar+ laser, the samples lost their birefringence, so the phase transition from N to I state was induced. Similar experiment conducted in our previous work [6,7,12] explained the mechanism of phase transition by Ar+ laser irradiation in terms of order-disrupting molecules Az through conformational changes. That means the phase transition can be induced in an Az-doped-LLC system in which Ar+ laser exposure directly decreased the order of the mixture through trans-cis-trans cycle photoisomerization of Az moiety.…”
Section: Phase Transition Of Llc By Thermal Effectsupporting
confidence: 73%
See 2 more Smart Citations
“…However, as shown in Fig.4 (b), when the Az-doped samples were irradiated with Ar+ laser, the samples lost their birefringence, so the phase transition from N to I state was induced. Similar experiment conducted in our previous work [6,7,12] explained the mechanism of phase transition by Ar+ laser irradiation in terms of order-disrupting molecules Az through conformational changes. That means the phase transition can be induced in an Az-doped-LLC system in which Ar+ laser exposure directly decreased the order of the mixture through trans-cis-trans cycle photoisomerization of Az moiety.…”
Section: Phase Transition Of Llc By Thermal Effectsupporting
confidence: 73%
“…Similarly, the gradient in surface tension can also be used to control the motion of glass rods in Az-doped polyethylene glycol films, as found by Su Ma et al [10]. However, Lohn, et al described the micron objects can be assembled by thermos-induced phase transition [2], whose driving force is also accorded with our previous work [6][7]12].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The glass rod rotated in the same direction as the cholesteric texture during the photoisomerization or thermal transition steps. A detailed study was also reported with the investigation of CLC-induced azobenzene dopants and fluorene-based overcrowded alkene dopants [65,68,140]. The authors pointed out that the rotational reorganization resulted from the conversion of the chiral molecular motor dopant to an isomer with a different HTP, leading to a change in the cholesteric pitch.…”
Section: Light-induced Mechanical Motions In Cholesteric Liquid Crystalsmentioning
confidence: 99%
“…More recently, research concerning the photocontrolled manipulation of microscale solid objects on the surface of a film of liquid crystal doped with a chiral azobenzene compound has been reported by Kurihara and coworkers [32,33]. Translational motion of a microscale object was observed in the racemic system (nematic liquid crystal doped with a racemic azobenzene compound or compensated nematic liquid crystal with cholesteric liquid crystal and chiral azobenzene compound) (Figure 2(b)).…”
Section: Photomanipulationmentioning
confidence: 94%